Center-Pivot-Irrigated Sorghum Silage Cost-Return Budget (Custom Harvested) - O'Brien, Daniel M.; Sartwelle III, James D. (My University, 1997)
This publication estimates the costs and returns associated with center-pivot-irrigated forage sorghum put up as silage in western Kansas.
MF998_1997_10
Keywords: MF998; Economics; Crops; MF